Effects of 6‐h exposure to low relative humidity and low air pressure on body fluid loss and blood viscosity. (28th March 2013) - Hashiguchi, N.; Takeda, A.; Yasuyama, Y.; Chishaki, A.; Tochihara, Y.
Abstract The purpose of this study was to investigate the effects of 6‐h exposure to low relative humidity (RH) and low air pressure in a simulated air cabin environment on body fluid loss (BFL) and blood viscosity. Fourteen young healthy male subjects were exposed to four conditions, which combined RH (10% RH or 60% RH) and air pressure (NP: sea level or LP: equivalent to an altitude of 2000 m). Subjects remained seated on a chair in the chamber for 6 h. Their diet and water intake were restricted before and during the experiment. Insensible water loss (IWL) in LP10% condition was significantly greater than in NP60% condition; thus, combined 10%RH and LP conditions promoted a greater amount of IWL. The BFL under the LP condition was significantly greater than that under the NP condition. Blood viscosity significantly increased under LP conditions. Increases in red blood cell counts (RBCs) and BFL likely contributed to the increased blood viscosity. These findings suggest that hypobaric‐induced hypoxia, similar to the conditions in the air cabin environment, may cause increased blood viscosity and that the combined low humidity and hypobaric hypoxia conditions increase IWL.